2010
DOI: 10.1124/dmd.110.035394
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Cremophor EL and Genetic Polymorphisms on the Pharmacokinetics of Paclitaxel and Its Metabolites Using a Mechanism-Based Model

Abstract: ABSTRACT:The formulation vehicle Cremophor EL has previously been shown to affect paclitaxel kinetics, but it is not known whether it also affects the kinetics of paclitaxel metabolites. This information may be important for understanding paclitaxel metabolism in vivo and in the investigation of the role of genetic polymorphisms in the metabolizing enzymes CYP2C8 and CYP3A4/CYP3A5 and the ABCB1 transporter. In this study we used the population pharmacokinetic approach to explore the influence of predicted Crem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 29 publications
2
24
0
Order By: Relevance
“…In addition, the CYP3A4*22 genotype has been shown to affect paclitaxel-induced neurotoxicity (de Graan et al, 2013). Furthermore, changes in the clearance of the CYP2C8 metabolite, 6a-hydroxypaclitaxel, is correlated to ABCB1 polymorphism and P-gp activity (Fransson et al, 2011). These findings indicate that P450-mediated paclitaxel metabolism and possibly specific metabolites are important factors affecting its clinical efficacy and toxicity and that drug-drug interactions caused by P450 inhibition may have important clinical implications for combination therapies.…”
Section: Introductionmentioning
confidence: 76%
“…In addition, the CYP3A4*22 genotype has been shown to affect paclitaxel-induced neurotoxicity (de Graan et al, 2013). Furthermore, changes in the clearance of the CYP2C8 metabolite, 6a-hydroxypaclitaxel, is correlated to ABCB1 polymorphism and P-gp activity (Fransson et al, 2011). These findings indicate that P450-mediated paclitaxel metabolism and possibly specific metabolites are important factors affecting its clinical efficacy and toxicity and that drug-drug interactions caused by P450 inhibition may have important clinical implications for combination therapies.…”
Section: Introductionmentioning
confidence: 76%
“…The same study also found evidence that the CYP2C8*4 and ABCC1 may have an effect on clearance, but found no significant influence of genetic variants in OATP, CYP3A4/5 or ABCB1. In contrast, a few minor studies have reported ABCB1 polymorphisms to affect either the kinetics of paclitaxel (Yamaguchi et al, 2006;Green et al, 2009) or of its hydroxy metabolites (Nakajima et al, 2005;Fransson et al, 2011).…”
Section: Introductionmentioning
confidence: 92%
“…Because of its lipophilic properties, paclitaxel is usually administrated as an infusion, dissolved in the formulation vehicle Cremophor EL, which has been shown to affect the kinetics of the drug (Sparreboom et al, 1996), and most likely the kinetics of the two primary hydroxy metabolites (Fransson et al, 2011). Binding of drug to Cremophor EL and proteins in the systemic and liver plasma compartments, (3a) and (3c), was assumed to be instantaneous by including an equation derived from population pharmacokinetic modeling by Henningsson et al (2001), describing the relation between total and unbound concentrations, (3b) and (3d).…”
Section: Model Developmentmentioning
confidence: 99%
“…However, the therapeutic response is always associated with toxic side effects, such as hypersensitivity reactions, pain at the injection site and dizziness. [1][2][3][4][5] In addition, it is difficult to apply paclitaxel to the clinic because of its extremely low solubility in water. Taxol ® , a mixture of 50% cremophor EL and 50% dehydrated alcohol (v/v), is the main dosage form for clinical administration of paclitaxel, which requires further 5 to 20-fold dilution with aqueous solutions such as 0.9% sodium chloride.…”
Section: Abstract Nanoparticle; Ovarian Cancer; Paclitaxel Therapymentioning
confidence: 99%
“…When the gross tumor reached 100-180 mm 3 , treatments were started, and this day was designated as day one. All mice were randomly divided into four groups with eight mice per group.…”
Section: Toxicity Evaluationmentioning
confidence: 99%